Weryfikacja istotności kryteriów oceny projektowania witryn internetowych za pomocą algorytmów genetycznych - Małachowski, Andrzej; Idzikowski, Maciej; Wasiak, Maciej (The Use of Genetic Algorithm in Choosing Most Important Criteria of Web Pages Design, 2006)
This article presents the results of the research which covers the design of corporate websites. It also verifies data aquired with the traditional metod with the genetic algorithms method.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (17); 2006; nr 1123, s. 232-241